Bilingual Acquisition of Morphology: Norwegian and Russian Influence on Children’s Sentence Repetition in Estonian - Vaks, Adele; Vihman, Virve-Anneli (Language and speech, 2025)
In this study, we investigate whether two structurally distinct languages, Norwegian and Russian, influence the use of Estonian morphosyntax by bilingual 5 to 7-year-olds. Using a sentence-repetition task, we tested the acquisition and use of Estonian morphosyntax by children acquiring Estonian alongside Norwegian and Russian, which differ in their use of morphological marking. We tested 69 children aged 4;9 to 7;10 (24 Estonian-Norwegian and 24 Russian-Estonian bilinguals, 21 Estonian monolinguals), using three sentence structures that vary across the languages (copula clauses, experiencer clauses, and complex conditional sentences). Quantitative results showed no significant differences between groups. Both groups were at ceiling for copula clauses, but they performed in opposite directions with the other two structures, suggesting possible effects of the other language. An error analysis revealed small differences in children’s use of experiencer and conditional constructions. Contrary to expectations, Norwegian-speaking bilinguals did not produce more errors of omission than of commission in either sentence type. Rather, they used a wider array of cases in the experiencer clauses than Russian-speaking children. In the conditional items, both groups exhibited a tendency to use indicative past in place of conditional present, transferring the use of past forms for conditional meanings from Norwegian or Russian. Other differences are discussed in light of language structure, Estonian exposure, and study design.